BUERGER ALLEN EXERCISE REVIEW ON PERIPHERAL CIRCULATION IN DIABETES MELLITUS PATIENTS: A LITERATURE REVIEW - La Ode Agustino Saputra; Muhammad Anwar Hafid; Ani Auli Ilmi; Hasnah Hasnah (Universitas Islam Negeri Alauddin Makassar, 2020)
Introduction: Diabetes mellitus is metabolic dysfunction that increasing the number of blood glucose with enhancement incidences. Increasing blood glucose levels for a long time causes chronic microvascular and neuropathic complications, and impaired peripheral circulation of the lower extremities. The actions that can be done in form of leg exercise, such as Buerger Allen exercise. Objectives: the study aim is to find out the effect of the Buerger Allen exercise on peripheral circulation of the lower extremity in patients with diabetes mellitus. Method: descriptive qualitative design with a literature review approach. The databases used are PubMed, Pro-Quest, DOAJ, and Google Scholar. Result: 86 articles were found. After the identification, screening, and eligibility process, 12 articles were obtained. The indicators are ABI values (9 articles), HbO2 and HbT concentrations (2 articles), and capillary refill time (1 article). Conclusion: Buerger Allen exercise significantly increases the level of peripheral perfusion pressure due to postural changes, modulation of gravity, and the application of muscle pump that increases the ABI values, increases HbO2 and HbT concentrations, and decreases the capillary refill time. Further study can examine the frequency and duration that is most appropriate in providing intervention, comparing Buerger Allen exercise with other foot exercise methods, and using a randomized control trial research method.